The effect of music intervention in decreasing pain and anxiety during outpatient hysteroscopy procedure: a systematic review and meta-analysis of randomized control trials - Mohamed Abd-ElGawad; Nada K. Abdelsattar; Mohamed Abdelmonem Kamel; Youstina Amin Sabri; Ethar Mohamed Fathy; Noha Abd El-Moez; Yasmeen Saeed Abdellatif; Ahmed A Metwally (BMC, 2023)
Abstract Background Hysteroscopy is a common outpatient procedure but procedural pain limits its use. Music could be used as a pain-relieving intervention. We performed a systematic review and meta-analysis to investigate the effect of music on pain and anxiety during outpatient hysteroscopy. Methods Four electronic databases were searched: PubMed, Scopus, Web of Science, and Cochrane Library, from inception to September 2022. We included only the Randomized Controlled Trials (RCTs) that investigated the effect of music on women who underwent outpatient hysteroscopy in reducing pain and anxiety levels compared to no music. We assessed the quality of included RCTs using the risk of bias tool 1 reported in the Cochrane Handbook of Systematic Reviews of Interventions. Data were pooled as the Mean Differences (MDs) with a 95% Confidence Interval (CI) in a random-effects model, using Review Manager 5.3 software. Also, we assessed the evidence of the results using the Grading of Recommendations Assessment, Development and Evaluation (GRADE). Results Three RCTs (540 women) were included. Music significantly reduced visual analogue scale (VAS) pain scores as well as State-Trait Anxiety Inventory (STAI) scores compared to controls (MD = -1.28; 95% CI [-2.19, -0.36]; P = 0.007) and (MD = -3.91; 95% CI [-6.98, -0.85]; P = 0.01) respectively. Also, the decrease in VAS score for pain was significantly greater in the music group (MD = 1.44; 95% CI [0.44, 2.45]; P = 0.005). However, the change in STAI showed no significant difference between the two groups. The GRADE ratings for all outcomes were very low. Conclusion Music is a potentially promising method for controlling pain for patients undergoing outpatient hysteroscopy; however, its effect in controlling anxiety is controversial.